Direct cyclopropanation of activated N-heteroarenes via site- and stereoselective dearomative reactions. Issue 6 (10th January 2020) - Lee, Jiyoun; Ko, Donguk; Park, Hyunju; Yoo, Eun Jeong
Abstract : A divergent cyclopropanation reaction has been accomplished via the dearomative addition of sulfur ylides to activated N-heteroarenes. Abstract : A divergent cyclopropanation reaction has been accomplished via the dearomative addition of sulfur ylides to activated N-heteroarenes. A series of biologically significant molecular skeletons was obtained by the direct cyclopropanation of quinolinium zwitterions. Furthermore, a straightforward synthetic route to optically enriched cyclopropane-fused heterocycles was developed using sulfur ylides as chiral nucleophiles in the 1, 4-dearomative reaction.